Teaching Materials Development Based Using Guided Discovery Model On Pythagoras Theorem Materials For Class Viii Smpn 4 West Bangkala, Jeneponto Regency - Mardhiah Mardhiah; Irmawati Irmawati; Baharuddin Baharuddin; St Ibrah Mustafa Kamal; Nurlaelah Nurlaelah (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This article discusses the development of mathematics teaching materials based on guided discovery models based on the material of the Pythagoras Theorem for Class VIII SMPN 4 West Bangkala, Jeneponto Regency. The purpose of this study was to determine the development of teaching materials based on guided discoveries based on the Pythagorean Theorem material for Class VIII SMPN 4 West Bangkala, Jeneponto Regency that were valid, practical and effective. The type of research performed is research and development (research and development). The Research Results Achieved (1) The validation results for teaching materials and all research instruments received an average overall validity of 4.14, which is in the valid category because it is in the interval 3.5 M 4.3. (2) The practical test resulting from the results of the teacher's questionnaire analysis for all aspects is 97%. In addition, the proportion of student answer questionnaires for all aspects is 89.45%. These numbers lie in the interval 85% RS 100% and can be classified as very positive (3) Effective, the results of the evaluation of the student learning outcome test are 80% classically completed and fall into the high category, so it can be concluded that the teaching materials which are based on a guided discovery of the material of the Pythagorean Theorem Class VIII SMPN 4 Bangkala Barat Jeneponto Regency, which meet the criteria of validity, practicability and effectiveness.